This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Stat 333  Assignment 2 Solutions  Fall 2011 1. (a) We have an even number of S s in n trials iff there is a failure in the 1st trial, and we have an even number of successes in remaining n 1 trials, or there is a success in the 1st trial, and we have an odd number of successes in remaining n 1 trials. Therefore, e n = P ( even number of Ss in n1 trials  1st trial is a failure ) P ( 1st trial is a failure ) + P ( odd number of Ss in n1 trials 1st trial is a success ) P ( 1st trial is a success ) = P ( even number of Ss in n1 trials ) P ( 1st trial is a failure ) + P ( odd number of Ss in n1 trials ) P ( 1st trial is a success ) = e n 1 (1 p ) + (1 e n 1 ) p = e n 1 q + (1 e n 1 ) p, n 1 where the second expression follows from the fact that we have independent trials and q = 1 p . (b) Note that e = 1 since we assume zero is even. Also, before we proceed, we rewrite the above expression as e n = ( q p ) e n 1 + p . We have G ( z ) = X n =0 e n z n = 1 + X n =1 e n z n = 1 + X n =1 [( q p ) e n 1 + p ] z n = 1 + ( q p ) X n =1 e n 1 z n + p X n =1 z n = 1 + ( q p ) z X k =0 e k z k + p X n =1 z n where k = n 1 = 1 + ( q p ) zG ( z ) + p z 1 z Therefore, G ( z ) = 1 + p z 1 z 1 ( q p ) z = 1 z (1 p ) (1 z )[1 ( q p ) z ] (c) When p = q = 0 . 5 , G ( z ) = 1 . 5 z 1 z = 1 + . 5 z 1 z = 1 + 0 . 5 X n =1 z n which implies that e n = 1 , n = 0 . 5 , n 1 1 2. Since d = 0 , D ( z ) = X n =0 d n z n = X n =1 d n z n = X n =1 P ( occurs on trial n ) z n Now, P ( occurs on trial n ) = n X k =1 P ( occurs on trial n  occurs first on trial...
View
Full
Document
 Fall '08
 Chisholm
 Probability

Click to edit the document details